Effects of Carbonated Soft Drink on Saliva pH in the Occurrence of Dental Caries - Santoso, Theofany L. A.; Wicaksono, Dinar A.; Gunawan, Paulina N. (Universitas Sam Ratulangi, 2022)
Abstract: One of the instantaneous lifestyle can be seen inter alia from the high level of soft drink consumption. Consumption of carbonated soft drinks produces a pH ranging from 2.4 to 4.07 which is classified as low. CO2 dissolved in carbonated soft drinks is thought to increase acidity, therefore, decrease the pH of saliva. The continuous decrease in salivary pH can lead to demineralization of tooth structure which triggers the occurrence of dental caries. This study aimed to determine the effect of soft drink consumption on salivary pH related to the incidence of dental caries. This was a literature review studi using four databases as follows: Google Scholar, PubMed, ScienceDirect, and ClinicalKey. The keywords were